The Relationship of Knowledge Level and Adolescents About Reproductive Health with Adolescent Reproductive Health Behavior - Ritonga, Fitriana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Adolescence is a dynamic developmental phase in an individual's life. This period is the transition from childhood to adulthood. During this period, there was rapid growth, including reproductive function, which affected the development of changes in physical, mental and social roles. Adolescence is also often called a critical period because, at that time when teenagers do not get the right guidance and information, problems often occur that can affect the future of adolescents. The purpose of the study was to determine the relationship between the level of knowledge and attitudes of adolescents about reproductive health with reproductive health behaviour of adolescents in grades 11 and 12 at SMA Negeri 4 Medan. In this study using a cross-sectional research design, the research subjects were 11th and 12th-grade students of SMA Negeri 4 Medan. The variables studied were the level of knowledge and attitudes of students. Data analysis using a quantitative approach was used to determine the distribution of the data, using univariable analysis, bivariable with Chi-square The results of the bivariable statistical test showed that there was a significant relationship between the level of knowledge and adolescent reproductive health behaviour (?2=18.2; p=0.00 RP=1.585; CI 95%=1.19-2.09), and there is a significant relationship between adolescent attitudes and reproductive health behaviour (?2=18.00; p=0.00 RP=1.570; 95% CI=1.19-2.09). knowledge and attitudes of adolescents, with adolescent reproductive health behaviour at SMA Negeri 4 Medan.